THE EFFECT OF JOB SATISFACTION AND JOB ENVIRONMENT ON TURNOVER INTENTION EMPLOYEES IN ENGINEERING AND SERVICES CONSTRUCTION SERVICES - Christina Catur Widayati; Purnamawati Helen Widjaja; Lia D (Dinasti Publisher, 2019)
This research is to know the influence of job satisfaction and job environment toward turnover intention level. The object of this research is employees or employees who work in construction engineering services and services company in Jakarta. This research was conducted on 66 respondents by using descriptive approach quantitative. Therefore, the data analysis used is Partial Least Square (PLS) analysis. The result of this research shows that job satisfaction variable give negative and significant influence to turnover intention. The job environment has a negative and significant impact on the turnover intention of construction engineering and services company in Jakarta. This is evidenced from the results of hypothesis testing (t test) which shows the value of the syndication of independent variables.